Zimbabwe : 2004 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that Zimbabwe's real GDP declined by 9.3 percent in 2003, and an additional broad-based decline is projected in 2004. Year-over-year inflation reached 600 percent during November 2003-February 2004. However, monthly inflation, which had reached 34 percent in November 2003, fell to 5 percent in April 2004 following a tightening of monetary policy and an appreciation of the exchange rate. Progress has been limited on structural reforms. Most price controls were removed after May 2003, and the fuel market was partially liberalized.